RATES OF APPLICATION OF MINERAL FERTILIZERS ON IRRIGATED TYPICAL SERIOZEMS WITH DIFFERENT LEVEL OF FERTILITY IN COTTON AND WINTER WHEAT GROWING (Academicia Globe: Inderscience Research, 2022)
The studies were carried out on old-irrigated typical sierozems formed on loess deposits of the II-III terrace of the upper part of the Gejigen River.